2022
DOI: 10.1038/s41467-022-31125-6
|View full text |Cite
|
Sign up to set email alerts
|

Evaporative water loss of 1.42 million global lakes

Abstract: The evaporative loss from global lakes (natural and artificial) is a critical component of the terrestrial water and energy balance. However, the evaporation volume of these water bodies—from the spatial distribution to the long-term trend—is as of yet unknown. Here, using satellite observations and modeling tools, we quantified the evaporation volume from 1.42 million global lakes from 1985 to 2018. We find that the long-term average lake evaporation is 1500 ± 150 km3 year−1 and it has increased at a rate of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(84 citation statements)
references
References 56 publications
3
81
0
Order By: Relevance
“…Multi annual averages, from 2012 to 2014, were equal to 5.33 mm.d −1 by our estimation, 5.40 mm.d −1 by derived evaporation (Fowe et al, 2015) and 5.38 mm.d −1 by GLEV (Zhao et al, 2022). Evaporation differences by these three methods are lower https://doi.org/10.5194/hess-2022-367 Preprint.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Multi annual averages, from 2012 to 2014, were equal to 5.33 mm.d −1 by our estimation, 5.40 mm.d −1 by derived evaporation (Fowe et al, 2015) and 5.38 mm.d −1 by GLEV (Zhao et al, 2022). Evaporation differences by these three methods are lower https://doi.org/10.5194/hess-2022-367 Preprint.…”
Section: Discussionmentioning
confidence: 64%
“…Precipitation is estimated by the Integrated Multi-satEllite Retrievals algorithm of the international satellite mission Global Precipitation Measurement (IMERG-GPM, Huffman et al, 2019). The data are provided by Google Earth Engine, through the "GPM: Global Precipitation Measurement (GPM) v6" collection, with a spatial resolution of 0.1 Global Lake Evaporation Volume (GLEV) dataset (Zhao et al, 2022) and Colorado pan evaporation data over a small reservoir (Boura) from Fowe et al (2015), are used for validation over the April 2012-April 2014 period.…”
Section: Datamentioning
confidence: 99%
“…We also see a smaller but salient intra-annual lake area ranges in Asia and in East Africa along the rift valleys and the Nile valley. In this case, the dominant driver remains the seasonal pattern of winter and changes within the single year of our study are harder to link to wider effects as in 13 . We then use the level 3 HydroBASINS vectors and sum the total areas in each basin, in ha, The total is then normalised by basin area, in km 2 .…”
Section: Figure 3 Global Scaling Relationships For Rivers and Lakes A...mentioning
confidence: 86%
“…Reservoir evaporation estimates can be extracted from two available global reservoir evaporation products produced by the Zhao et al (2022) and Tian et al (2022). These studies covered a portion of the reservoirs we studied and used the same robust algorithm by Zhao et al (2019) (3) shortwave radiation [MJ m −2 d −1 ]), for the evaporation rate calculation.…”
Section: Data and Methodology For Generating Reservoir Evaporationmentioning
confidence: 99%
“…These studies covered a portion of the reservoirs we studied and used the same robust algorithm by Zhao et al (2019) (3) shortwave radiation [MJ m −2 d −1 ]), for the evaporation rate calculation. In previous studies (Zhao et al, 2022;Tian et al, 2022), the TerraClimate dataset (Abatzoglou et al, 2018) has been shown to be the most appropriate meteorological dataset for reliable estimates of reservoir evaporation rates compared to other global datasets. Thus, we adopted the TerraClimate to generate meteorological data time series by averaging gridded forcing data within reservoir shapefiles.…”
Section: Data and Methodology For Generating Reservoir Evaporationmentioning
confidence: 99%